CONFLICTO SOCIAL, HUMOR Y LENGUAJE EN LA LITERATURA Y EL PROYECTO EDITORIAL DE WASHINGTON CUCURTO. - Ros, Ofelia (Latin American Research Review, 2015)
This article analyzes social conflict, humor, and language in Washington Cucurto's literature and in the production of the publishing house Eloísa Cartonera. It emphasizes the relation of Cucurto's work to the Argentinean crisis of 2001-a period of instability in which sociopolitical, economic, and cultural configurations were originally questioned by social and artistic collectives. Cucurto's humor combines oral speech with phrases that do not belong to it but to poetry, opening the space for the satire and tragedy of Argentinean social reality at the end of the millennium. This genre, which Cucurto dubs realismo atolondrado (scatterbrained realism), introduces a "disturbing strangeness" within the automatized social practices by which the violence, the racism, and the xenophobia directed toward local and foreign immigrants are naturalized.